OPTIMALISASI PENGGUNAAN LAHAN DAN IMPLIKASINYA TERHADAP KETAHANAN PANGAN : Studi di Komplek Akademi Militer Magelang - Muslim, Khairul; Sudrajat; Zubaidi, Ahmad (PPM Sdirjianbang Akademi Militer, 2024)
Food security is one of the most important things for a country, including Indonesia. This study aims to explain the various factors or constraints of land use, the optimization that has been or is expected from land managers, and the resulting implications at the Panca Arga Kesatuan dormitory at the Magelang Military Academy. The method used was a qualitative survey with in-depth interviews using purposive random sampling and data triangulation for analysis. In land use there are factors that hinder such as expensive fertilizer prices, unstable selling prices, different land forms, availability of infrastructure, pests and knowledge for each cultivator. Land cultivators also do various things to optimize their yields by joining the farming community in the area around the Panca Arga Military Academy dormitory, prioritizing selling crops to residents of the Panca Arga Unitary Military Academy dormitory, attending counseling or discussions about agriculture from people who are competent in the field prepared pesticides and build adequate infrastructure. The benefits that land cultivators get are numerous, such as being closer to other members of the soldiers, increasing their income, and also maintaining their health while not serving as soldiers. The Magelang Military Academy Unity and the community also benefit from the use of the land.